GPX7 Is Targeted by miR-29b and GPX7 Knockdown Enhances Ferroptosis Induced by Erastin in Glioma - Zhou, Yan; Wu, Haiyang; Wang, Fanchen; Xu, Lixia; Yan, Yan; Tong, Xiaoguang; Yan, Hua (Frontiers in Oncology, 2022)
Background Glioma is a lethal primary tumor of central nervous system. Ferroptosis is a newly identified form of necrotic cell death. Triggering ferroptosis has shown potential to eliminate aggressive tumors. GPX7, a member of glutathione peroxidase family (GPXs), has been described to participate in oxidative stress and tumorigenesis. However, the biological functions of GPX7 in glioma are still unknown. Methods Bioinformatics method was used to assess the prognostic role of GPX7 in glioma. CCK8, wound healing, transwell and cell apoptosis assays were performed to explore the functions of GPX7 in glioma cells. In vivo experiment was also conducted to confirm in vitro findings. Ferroptosis-related assays were carried out to investigate the association between GPX7 and ferroptosis in glioma. Results GPX7 was aberrantly expressed in glioma and higher expression of GPX7 was correlated with adverse outcomes. GPX7 silencing enhanced ferroptosis-related oxidative stress in glioma cells and the loss of GXP7 sensitized glioma to ferroptosis induced by erastin. Furthermore, we found that miR-29b directly suppressed GPX7 expression post-transcriptionally. Reconstitution of miR-29b enhanced erastin sensitivity, partly via GPX7 suppression. Conclusions Our study clarified the prognostic role of GPX7 in glioma and preliminarily revealed the role of GPX7 in ferroptosis, which may be conducive to the exploration of therapeutic targets of glioma.